Termite Nest Associated Bacillus siamensis YC-9 Mediated Biocontrol of Fusarium oxysporum f. sp. cucumerinum - Zhou, Lingfeng; Wang, Junyong; Wu, Fei; Yin, Caiping; Kim, Ki Hyun; Zhang, Yinglao (Frontiers in Microbiology, 2022)
The antagonistic potential of bacteria obtained from the nest of Odontotermes formosanus was assessed against Fusarium oxysporum f. sp. cucumerinum (FOC). Of 30, seven termite nest-associated bacteria strains had biocontrol potential. Among them, the strain YC-9 showed the strongest antifungal activity toward FOC. Phylogenetic analysis of the 16S rRNA amplified product of YC-9 revealed its identification as Bacillus siamensis. The in vivo antifungal activity experiment showed that the application of YC-9 at 108 cfu/ml significantly reduced the cucumber wilt incidence with a control efficacy of 73.2%. Furthermore, plant growth parameters such as fresh weight, dry weight, plant height, and root height were significantly improved by 42.6, 53.0, 20.8, and 19.3%, respectively. We found that inoculation with B. siamensis YC-9 significantly increased the activity of defensive enzymes such as peroxidase (POD), polyphenol oxidase (PPO), and phenylalanine ammonia-lyase (PAL) in diseased cucumber roots, thereby raising the resistance. PCR using gene-specific primers revealed that B. siamensis YC-9 contains biosynthetic genes for known antibiotics, including bacillomycin, iturin, and surfactin. Chemical analysis of the cultivation of B. siamensis YC-9 resulted in the isolation of five metabolites, including hexadecanoic acid (1), cyclo-(L-phenylalanylglycine) (2), cyclo-(L-trans-Hyp-L-Leu) (3), C15-surfactin (4), and macrolactin A (5), the structures of which were identified by the analysis of NMR spectroscopic data and MS. Among them, the compound 4 showed significant antifungal activity against conidial germination of FOC with an IC50 value of 5.1 μg/ml, which was comparable to that of the positive control, cycloheximide (IC50 value of 2.6 μg/ml). Based on these findings, this study suggests that termite-nest associated B. siamensis YC-9 could be a potential biological control agent for integrated control of soil-borne diseases like cucumber Fusarium wilt.